2021
DOI: 10.3386/w29010
|View full text |Cite
|
Sign up to set email alerts
|

A Denial a Day Keeps the Doctor Away

Abstract: for exceptional research assistance, and we thank numerous seminar audiences for helpful comments. A previous draft of this article circulated under the title "The Costs of Payment Uncertainty in Healthcare Markets". NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…That study also found that a more important mediator of survivability was the stage of diagnosis. In context with our findings, if private or Medicare insurance coverage was expanded or if Medicaid eased the administrative burden physicians face, far fewer women from racial and ethnic minority groups would receive a diagnosis of advanced-stage cancer and, thus, would have a higher survivability.…”
Section: Discussionsupporting
confidence: 65%
“…That study also found that a more important mediator of survivability was the stage of diagnosis. In context with our findings, if private or Medicare insurance coverage was expanded or if Medicaid eased the administrative burden physicians face, far fewer women from racial and ethnic minority groups would receive a diagnosis of advanced-stage cancer and, thus, would have a higher survivability.…”
Section: Discussionsupporting
confidence: 65%
“…Whether all mental health care will be covered under this provision has not yet been determined. Other policy solutions are needed to retain (and recruit) practitioners in networks, possibly through reimbursement and a reduction in administrative burden . The high rate of denials of claims for mental health treatment under private insurance suggests this may be a relevant factor underlying low participation among mental health practitioners …”
Section: Discussionmentioning
confidence: 99%
“…Germany 16% of the claims submitted are rejected and eventual indemnifications average only 63% of initial claims. Similarly, Dunn et al (2021) report that insurers deny (at least partially) 25% of Medicaid claims, while Briggs and Tonetti (2022) find that consumers expect to receive only a fraction of the promised payout for annuity, life and long-term care insurance.…”
Section: Nonperformance Riskmentioning
confidence: 99%